Cyber Sexual Harassment Terhadap Perempuan Di Media Sosial Perspektif Hukum Pidana Positif Dan Hukum Pidana Islam - Nufus, Tsulis Zakiyyatun; Najmudin, Deden; Azazy, Yusuf (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
Social media has significantly influenced the evolution of modern crimes, including cyber sexual harassment against women. This study aims to analyze the crime of cyber sexual harassment from the perspective of Indonesian positive criminal law and Islamic criminal law. The research employs a normative juridical method with a statutory and conceptual approach, including the analysis of maqāṣid al-syarī‘ah principles in Islam. The findings indicate that under Indonesian positive law, such acts can be prosecuted through the Criminal Code (KUHP), the Electronic Information and Transactions Law (ITE Law), and Law No. 12 of 2022 concerning Sexual Violence Crimes (TPKS Law). In Islamic criminal law, this behavior is categorized as fahisyah and falls under jarimah subject to ta'zir sanctions. Both legal frameworks emphasize the protection of women's dignity and support both punitive and preventive approaches. The integration of both perspectives offers a comprehensive legal response to combat sexual violence against women in digital spaces.